Chemometrics in Pharmaceutical Formulation: A Two-Decade Bibliometric Review (2005-2025) - Puspitasari, Lia; Larasati, Rizky Dwi; Maharani, Zahra Ayu (Sciences of Pharmacy, 2026)
Chemometrics is essential in modern pharmaceutical development for enhancing analysis and quality control. Despite its importance, the evolutionary trajectory and thematic shifts of chemometrics within pharmaceutical formulation have not been comprehensively synthesized. This study aims to explore publication trends, scientific collaborations, and keywords in research related to the application of chemometrics to pharmaceutical formulations, using a bibliometric approach. Data were retrieved from Scopus (2005–2025) using a structured search strategy focusing on "pharmaceutical formulation", "drug formulation", and "pharmaceutical development". The search was limited to English-language original articles or reviews. Bibliometric mapping was performed using VOSviewer and the Bibliometrix R-package, applying a minimum keyword occurrence of 5, full counting method, and association strength normalization. A total of 516 documents were identified. Publications have increased significantly in the last decade, with research articles being the dominant document type. Egypt and the United States are the countries with the highest contribution and citation impact. The Journal of Pharmaceutical and Biomedical Analysis is ranked highest in terms of the number of publications and influence. Khan, Mansoor A., is the most productive author, while the Faculty of Pharmacy at Cairo University and the FDA are the most productive organizations. Keyword analysis revealed various main themes and a division into seven clusters, highlighting an evolutionary shift from traditional analysis toward Process Analytical Technology (PAT) and Quality by Design (QbD). These findings highlight the importance of cross-disciplinary collaboration and the potential for further exploration of novel approaches in pharmaceutical product development.